Molecular phylogenetic study on genus Christella of thelypteridaceae (Pteridophyta) in Sabah by using rbcL sequence gene - Shamimah Parveen Abdul Rahman (2008)
There are six species under Genus Christella obtainable in Sabah. For this study, only four species were analyzed; Christella arida, Christella subpubescens, Christella sp. l and Christella sp. 2. For Christella sp. l and Christella sp. 2, identification process only successful till genus level. Besides determining DNA sequences of taxa in Christella, establishing phylogenetic relationship for Genus Christella is the main objective of the study. Constructing phylogenetic tree becomes possible by using rbcL sequence gene. The purpose of using rbcL gene is because it is sufficient to study phylogenetics relationship at the species level or to review ferns phylogenetics relationship. DNA sequences were analysed by using the PAUP* version 4.0 beta 10 for Macintosh computer programme to reveal relationship among studied species. Nucleotides sequences were edited using BioEdit computer programme and inserted into PAUP* for further analysis. Two analyses; Maximum Parsimony (MP) and Neighbor Joining (NJ) interested in this study. By comparing, both methods show similar results in separation of the studied samples according to the species nature. For MP method, it proves Christella sp. 1 as misidentified species due to exclusion from Christella Glade. This depicts more methods should be analysed for better output. Thus, proving molecular data agree with morphological data to build phylogenetic tree.